Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am having a doubt on an example on Conway's "Funtions of one Complex Variables". At example 2.9, page 117. At some point, it is stated that, since $$ a+\cos(\theta)=\dfrac{z^2+2az+1}{2z} $$ it must imply that $$ \int_0^{\pi}\dfrac{d\theta}{a+cos(\theta )}=\dfrac{1}{2}\int_0^{2\pi}\dfrac{d\theta}{a+cos(\theta)}=-i\int_{\gamma}\dfrac{dz}{z^2+2az+1} $$ where $\gamma (t)=e^{it}$, $t\in \left[0,2\pi \right]$.

I could get all that, except for what happens between the last two integrals; I think that there should be a "$2z$" before the $dz$, but when I insert it there the calculations doesn't end up right. Can someone explain me what I'm missing?

Thanks.

share|improve this question

2 Answers 2

up vote 2 down vote accepted

$$\int\frac{d\theta}{2a+2\cos\theta}=\int\frac{d\theta}{2a+e^{i\theta}+e^{-i\theta}}=\int\frac{dz}{iz}\cdot\frac{1}{2a+z+\frac{1}{z}}.$$ Then $$\int\frac{dz}{iz}\cdot\frac{1}{2a+z+\frac{1}{z}}=-i\int\frac{dz}{z^2+2az+1}.$$

share|improve this answer
    
Great! Thank you. –  Marra Feb 13 '13 at 3:08

$$a+\cos(\theta)=\dfrac{z^2+2az+1}{2z}\Longrightarrow -\sin\theta\,d\theta=\left(\frac{1}{2}-\frac{1}{2z^2}\right)dz=\frac{z^2-1}{2z^2}dz\Longrightarrow$$

$$d\theta=-\frac{z^2-1}{2z^2\sin\theta}dz=-\frac{z^2-1}{2z^2\sqrt{1-\cos^2\theta}}dz$$

But

$$1-\cos^2\theta=1-\left(\frac{z^2+2az+1}{2z}-a\right)^2=1-\left(\frac{z^2+1}{2z}\right)^2=$$

$$=-\frac{(z-1)^2(z+1)^2}{4z^2}\Longrightarrow d\theta=\frac{z^2-1}{2z^2}dz\frac{2z}{z^2-1}=\frac{dz}{z}$$

so

$$\frac{1}{2}\int\limits_0^{2\pi}\frac{d\theta}{a+\cos\theta}=\frac{1}{2}\int\limits_\gamma\frac{dz}{z}\frac{2z}{z^2+2az+1}=\ldots$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.